2020
DOI: 10.1007/978-3-662-61692-5
|View full text |Cite
|
Sign up to set email alerts
|

Medikamente in der Schmerztherapie

Abstract: Die Deutsche Nationalbibliothek verzeichnet diese Publikation in der Deutschen Nationalbibliografie; detaillierte bibliografische Daten sind im Internet über http:// dnb.d-nb.de abrufbar. © Springer-Verlag GmbH Deutschland, ein Teil von Springer Nature 2020 Das Werk einschließlich aller seiner Teile ist urheberrechtlich geschützt. Jede Verwertung, die nicht ausdrücklich vom Urheberrechtsgesetz zugelassen ist, bedarf der vorherigen Zustimmung des Verlags. Das gilt insbesondere für Vervielfältigungen, Bearbeitun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…It can be assumed that the respective medications taken have a symptom-reducing effect. In addition, a combination of two NSAIDs, which were taken most frequently by the respondents, is not recommended due to a small increase in analgesic effect but a notable increase in side effects [32]. The knowledge of Ds and DAs on this subject could explain why in most cases only one agent was taken.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that the respective medications taken have a symptom-reducing effect. In addition, a combination of two NSAIDs, which were taken most frequently by the respondents, is not recommended due to a small increase in analgesic effect but a notable increase in side effects [32]. The knowledge of Ds and DAs on this subject could explain why in most cases only one agent was taken.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of medication intake showed that Ds took their medication more irregularly but also more frequently as needed, depending on the region, while the DAs took their medication more frequently on a weekly basis. One reason for this is that the most commonly taken drugs from the NSAID class are not taken regularly over a long period of time because of the possible adverse effects; these include asthma attacks, increased risk of cardiovascular events or the loss of cytoprotective prostaglandins and the associated damage to the gastric and intestinal mucosa [33]. Since DAs took their medication more frequently on a weekly basis and Ds more frequently as needed, hypothesis 3 has to be rejected.…”
Section: Discussionmentioning
confidence: 99%
“…The main analgesics administered were tramadol, tilidine, piritramide, oxycodone, and remifentanil. To make the different drugs comparable, a conversion to their morphine equivalents was performed based on (22,23) as follows: 1 mg morphine ≅ 0.1 mg tramadol/tilidine ≅ 0.7 mg piritramide ≅ 2 mg oxycodone ≅ 100 mg remifentanil/fentanyl ≅ 1,000 mg sufentanil. The average time the patients spent in intermediate care was about 22.8 h, the average number of analgesic administrations was 10.4 with an average dose of 5.45 mg (converted to morphine equivalents).…”
Section: Procedures and Morphine Equivalentsmentioning
confidence: 99%
“…Indications include mild to moderate pain, postoperative pain, and tumor pain. The clinical duration of action is 4 to 6 h. The daily dosage is calculated as 10 to 15 mg/kg, with a maximum dose of 60 mg/kg [22]. Generally, adults are given 500 to 1000 mg intravenously every 6 h or a dose of 4 g per 24 h (continuous use) as postoperative analgesia.…”
Section: Analgesia and Sedation Analgesicsmentioning
confidence: 99%